Octomeria candidae (Orchidaceae: Pleurothallidinae), a new species from the Cordillera del Cóndor, Ecuador - Vélez-Abarca, Leisberth (2020)
A new species of Octomeria from southern Ecuador was found during an investigation on the orchids of the Cordillera del Cóndor. Octomeria candidae is described and illustrated; likewise, information on its distribution, habitat and conservation status is provided. The new proposed taxon is morphologically similar to O. estrellensis, from which it differs by its creeping habit, the narrowly ovate, long-acuminate sepals and petals, and the yellow lip with an acute apex. Key Words: Mining activities, New orchid species, Octomeria estrellensis, Orchid conservation, Zamora Chinchipe